2018
DOI: 10.1002/jsfa.8856
|View full text |Cite
|
Sign up to set email alerts
|

Shelf‐life dating of shelf‐stable strawberry juice based on survival analysis of consumer acceptance information

Abstract: Colour changes of strawberry juice during storage are shelf-life limiting. Combining ASLT with acceptability testing allowed to gain faster insight into the change in colour-based acceptability and to perform shelf-life predictions relying on scientific data. An analytical marker is a convenient tool for shelf-life predictions in the context of ASLT. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In addition, it is noteworthy to mention that the perceived differences in strawberry juice aroma, as shown in this work, are not necessarily linked to an unacceptable product. Previous related work showed that the aroma-based acceptance of strawberry juice was not affected by storage at 20 °C for 32 weeks (Buvé et al, 2018b). In other words, consumers will not disapprove strawberry juice based on its aroma when stored at ambient conditions.…”
Section: Odour Activity Valuesmentioning
confidence: 93%
“…In addition, it is noteworthy to mention that the perceived differences in strawberry juice aroma, as shown in this work, are not necessarily linked to an unacceptable product. Previous related work showed that the aroma-based acceptance of strawberry juice was not affected by storage at 20 °C for 32 weeks (Buvé et al, 2018b). In other words, consumers will not disapprove strawberry juice based on its aroma when stored at ambient conditions.…”
Section: Odour Activity Valuesmentioning
confidence: 93%
“…The consumer acceptability decreased with increasing storage time, showing a relation between the product’s acceptability and color. Buvé et al [ 17 ] and Gössinger et al [ 45 ] reported that color is a critical quality parameter in consumers’ acceptance of strawberry-based products. The reduction rate of the color-based acceptance of the strawberry leather samples was mainly dependent on the storage RH.…”
Section: Resultsmentioning
confidence: 99%
“…Although the consumers’ acceptance/rejection test for shelf life prediction of food is the most suitable tool, it is expensive, time-consuming, and difficult to perform routinely by food companies. Thereby, it would be more effortless for food industries to have an instrumental attribute correlated with consumer acceptability, which can be used as an indicator of the shelf life prediction [ 17 , 21 ]. This study carried out a linear correlation analysis between the strawberry leather consumer rejection probability and physicochemical properties ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only in a few studies was a real product indeed provided (Giménez et al, 2008;Wansink & Wright, 2006). There is no clear evidence related to the role of sensory perception accompanied by label information in a consumer's apprehension of freshness and his or her resulting rejection of food (Buvé et al, 2018;Thompson et al, 2018;Van Boxstael et al, 2014).…”
Section: Introductionmentioning
confidence: 99%